Potensi Kepemimpinan Sultan Ageng Tirtayasa untuk Mendukung Penguatan Berkebinekaan Global pada Profil Pelajar Pancasila dalam Pembelajaran Sejarah di SMA - Ardiansyah, Ilham; Wahyudi, Deny Yudo (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
History education in the Merdeka Curriculum plays an important role in shaping the character of students based on Pancasila values, especially the dimensions of global diversity, such as respect for culture and inclusivity. Historical figures such as Sultan Ageng Tirtayasa from the Banten Sultanate can be used as teaching materials to instill these values. In facing the challenges of intolerant attitudes and a lack of respect for culture that are rampant in the world of education, history learning can be a forum for shaping the character of students who respect culture through intracurricular activities. This study aims to identify the leadership potential of Sultan Ageng Tirtayasa to support the strengthening of global diversity in the profile of Pancasila students and to design history learning by incorporating this potential into it. The method used in this study is a literature study, where qualitative data is collected through analysis of relevant literature. This study found that Sultan Ageng Tirtayasa was a leader who respected culture, was able to communicate interculturally, reflected, and was responsible for the experience of diversity and social justice in leading the Banten Sultanate as a multicultural center of trade and culture. The leadership values ​​of Sultan Ageng Tirtayasa are very relevant to today's education, especially in forming an attitude of mutual respect between cultures that follows the Pancasila Student Profile. The leadership values ​​of Sultan Ageng Tirtayasa have great potential to be taught to students as part of history learning. By designing history learning that includes global diversity values ​​in learning materials, it can support the strengthening of the character of students who are globally diverse and deeply rooted in Pancasila values.